Did population differences in human pelvic form evolve by drift or selection? - Philipp Mitteroecker; Nicole DS Grunstra; Ekaterina Stansfield; Lukas Waltenberger; Barbara Fischer (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Pelvic dimensions differ, on average, among modern human populations. Some recent studies have reported that population differences in pelvic form evolved mainly by neutral processes, without considerable natural selection. This is a surprising claim given the many important functions of the human pelvis. This article re-evaluates this claim through a review of the medical literature and a new analysis of the data from which these results were obtained. We show that variation in modern pelvic form correlates with the risks of obstructed labour, pelvic floor disorders such as incontinence and prolapse, and numerous orthopaedic disorders that impair walking. Comparative population studies also document adaptations of human body form and pelvic dimensions to climatic conditions. However, these various and partly antagonistic selective forces on the human pelvis are not homogeneous across populations. They depend not only on climatic differences, but also on maternal and foetal body size, pelvic floor tissue properties, diet, lifestyle and the resulting metabolic capacities, as well as on obstetric practices and health care, all of which vary across human populations. Given the relatively rapid evolution of polygenic quantitative traits, we propose that pelvic dimensions have evolved different "compromise solutions" in different populations in response to local selective regimes. The results from a reanalysis of a large published global dataset on human pelvic canal dimensions clearly support this view.